2018
DOI: 10.1002/joa3.12036
|View full text |Cite
|
Sign up to set email alerts
|

Not all rotors, effective ablation targets for nonparoxysmal atrial fibrillation, are included in areas suggested by conventional indirect indicators of atrial fibrillation drivers: ExTRa Mapping project

Abstract: BackgroundEffects of nonparoxysmal atrial fibrillation (non‐PAF) ablation targeting complex fractionated atrial electrogram (CFAE) areas and/or low voltage areas (LVAs) are still controversial.Methods and ResultsA recently developed online real‐time phase mapping system (ExTRa Mapping) was used to conduct LVA mapping and simultaneous ExTRa and CFAE mapping in 28 non‐PAF patients after pulmonary vein isolation (PVI). Nonpassively activated areas, in the form of meandering rotors and/or multiple wavelets assumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
83
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 21 publications
3
83
0
Order By: Relevance
“…This patient with persistent AF changed to common AFL immediately after RF applications for NPAs detected by the online real‐time phase mapping system. Recently, Ashihara et al have developed an online real‐time phase mapping system (ExTRa Mapping TM ; Nihon Kohden Co.) . This phase mapping system is characterized by the automatic creation of each phase map movie based on the 5‐second wave dynamics during AF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This patient with persistent AF changed to common AFL immediately after RF applications for NPAs detected by the online real‐time phase mapping system. Recently, Ashihara et al have developed an online real‐time phase mapping system (ExTRa Mapping TM ; Nihon Kohden Co.) . This phase mapping system is characterized by the automatic creation of each phase map movie based on the 5‐second wave dynamics during AF.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the rotational activations was quantitatively assessed according to the value of the %NP and the distribution of the NPAs within the LA could be evaluated in real‐time. Although the recording time of “5 seconds” was likely short, time‐reproducibility of %NP was high, which would enable the rapid and accurate AF rotor mapping . In contrast, development and progression of atrial fibrosis are considered to be the substrate for AF perpetuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CFAE and LVA may be associated with rotors or abnormal substrate, they are indirect indicators of AF drivers. A study using a phase mapping system revealed that rotors and multiple wavelets did not always correlate with CFAEs and LVAs . Although efficacy of ablation of CFAEs and LVAs is controversial at the moment, they may attract attention again in future by advance of mapping technology.…”
mentioning
confidence: 99%
“…On the other hand, Ashihara et al have developed a novel online real‐time phase mapping system (ExTRa Mapping ™ ; Nihon Kohden Co.) based on the 5‐second wave dynamics during AF . They indicated that AF was mostly driven by spatiotemporally meandering rotors, rather than stationary stable rotors.…”
mentioning
confidence: 99%